Jihad: Meaning, Essence, and Contextualization of Revolutionary Experience Hadratussyaikh K.H. Hasyim Ash'ari - Taufiqurrohman, Muhammad; Islami, Aprilia Nur; Muhaemin, Muhaemin; Hasanah, Sri Nur (Asyahid Journal of Islamic and Quranic Studies (AJIQS), 2022)
The term jihad has various meanings, not only connoting the meaning of "physical movement" and homogeneity. However, it can be meaningful according to the context of social and mental change, both evolution and revolution. The socio-political and ideological context therefore greatly influences the meaning of jihad which has implications for behavior and actions, such as its relationship with fighting for human rights and freedom. In this article, it is concluded that jihad (struggle) is one of the three important components according to Hadratussyaikh K.H. Hasyim Asy'ari. First, the momentum of the Netherlands and its status as a non-Muslim who wants to control Indonesia after declaring independence. Second, Hadratussyaikh's extensive mass mobilization structure, both official and unofficial. Third, framing dissatisfaction with the presence and policies of the Netherlands with the belief that maintaining independence is part of jihad fi sabilillah as well as a spirit of da'wah that is equivalent to revolution. Keywords: Da'wah, Social Change, jihad fi sabilillah, revolution   Abstrak Istilah jihad memiliki makna beragam, bukan hanya berkonotasi makna “gerakan fisik” dan homogen. Namun, dapat bermakna sesuai konteks perubahan sosial maupun mental, baik evolusi maupun revolusi. Konteks sosio-politik maupun ideologi karenanya sangat mempengaruhi makna jihad yang berimplikasi pada perilaku dan tindakan, seperti hubungannya dengan memperjuangkan hak-hak asasi dan kemerdekaan manusia. Pada artikel ini, disimpulkan bahwa jihad (perjuangan) menjadi salah satu dari tiga komponen penting menurut Hadratussyaikh K.H. Hasyim Asy’ari. Pertama, momentum Belanda dan statusnya sebagai non-muslim yang ingin menguasai Indonesia pasca memproklamasikan kemerdekaan. Kedua, struktur  mobilisasi massa Hadratussyaikh yang luas, baik yang resmi maupun tidak resmi. Ketiga, framing ketidakpuasan terhadap kehadiran dan kebijakan Belanda dengan berkeyakinan bahwa mempertahankan kemerdekaan merupakan bagian dari jihad fi sabilillah sekaligus spirit dalam dakwah yang disetarakan dengan revolusi. Kata Kunci: Dakwah, Perubahan Sosial, jihad fi sabilillah, revolusi